WORK MOTIVATION: SYSTEMATIC LITERATURE REVIEW (SLR) WITH BIBLIOMETRIC - Firmansyah; Sopiah (Universitas Islam Malang, 2025)
Work motivation is defined as a state of individual personality that fosters a desire to carry out certain activities in order to achieve the expected goals. For this reason, this research (SLR) was conducted to analyze the findings from data in the form of scientific journals regarding work motivation. SLR in this study was carried out using the prism method with the help of bibliometric tools as an analytical tool. Data collection is done by determining the database or data source: ScienceDirect, Taylor and Francis, Elsevier, Emeral, and SAGE. As such, 45 articles were analyzed in this systematic review process. This finding shows that the co-authorship collaboration of each author has a relationship with each other in conducting research related to work motivation. Co-occurrence (network visualization) was found in the displays described in the network visualization. These results indicate that there are many variations in the relationship between work motivation and other problems that can be explored and developed further in the context of work motivation. Co-occurrence (overlay visualization) results show that the bluer the keyword cluster, the longer the research time has been carried out, while the yellower the keyword cluster, the more recent the research.